Bridging Policy and Practice in Competency Assessment of Indonesian Proficient Teachers: A Mixed Methods Gap Analysis - Blegur, Jusuf; Lumba, Andreas J. F.; Berliana, Berliana; Siki, Intan Christine Adriani; Angoy, Raisalam D. T. (FKIP Universitas Lampung, 2025)
Bridging Policy and Practice in Competency Assessment of Indonesian Proficient Teachers: A Mixed Methods Gap Analysis. Objective: This study aims to analyze the need for developing teacher competency assessment instruments for proficient teachers. Method: This study used a mixed-methods approach with a convergent design. It begins by analyzing 457 Scopus-indexed publications from the past 46 years, identified through the keywords “teacher AND competency AND assessment AND instrument.” A content analysis of five selected publications relevant to Indonesia was conducted to align the desired competencies of proficient teachers with the Regulation of the Director General of Teachers and Education Personnel Number 2626/B/HK.04.01/2023. To further explore gaps in existing instruments, the study utilized VOSviewer for visualization and additional content analysis, considering code, category, and theme. Findings: The findings reveal that current teacher assessment instruments in Indonesia are not yet aligned with the 2023 regulation, particularly lacking indicators focused on the competency of “evaluating and designing improvements.” This is a critical performance area highlighted in the new policy framework, which aims to enhance student-centered education. Conclusions: As a result, it is concluded that this study highlights a clear and urgent need for the development of more contextualized assessment instruments that reflect updated regulatory expectations, address actual teacher performance needs, and support improved learning outcomes. These insights serve as a vital foundation for future research and policy-driven development of teacher assessment tools in Indonesia. Keywords: competency assessment instruments, teacher competency, teacher competency instruments, proficient teacher competency.